2022
DOI: 10.31234/osf.io/yqust
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Advancing multi-timeframe developmental research through combining long-term cohort and ecological momentary assessment studies: The Decades-to-minutes (D2M) study

Abstract: Within developmental science, there is a gap between our understanding of long-term ‘developmental’ processes, investigated via traditional longitudinal cohort designs, and our understanding of short-term ‘momentary’ processes, investigated via lab-based studies or, increasingly, via ecological momentary assessment (EMA) methods. To bridge this gap, multi-timeframe studies that link momentary processes to long-term developmental trajectories are needed. One promising approach is to embed studies of momentary p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…The Decades‐to‐Minutes (D2M) study (see Murray, Speyer, et al., 2022) took place shortly after the age 20 main wave of z‐proso in 2018. During the data collection for this z‐proso wave, participants were invited to take part in an additional EMA sub‐study.…”
Section: Methodsmentioning
confidence: 99%
“…The Decades‐to‐Minutes (D2M) study (see Murray, Speyer, et al., 2022) took place shortly after the age 20 main wave of z‐proso in 2018. During the data collection for this z‐proso wave, participants were invited to take part in an additional EMA sub‐study.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were n = 255 young adults from the ‘Decades‐to‐minutes’ (D2M) sub‐study (Murray et al., 2020) of the longitudinal Zurich Project on Social Development from Childhood to Adulthood (z‐proso; Ribeaud et al., 2022). D2M is an EMA sub‐study that aims to illuminate the long‐term developmental and daily life proximal influences on mental health and behaviour problems (Murray, Speyer, et al., 2022). Z‐proso began in 2004 when participants were aged 7 and used a stratified random sampling procedure to select schools from Zurich, Switzerland.…”
Section: Methodsmentioning
confidence: 99%
“…Previous analyses have explicitly compared D2M to the broader z‐proso cohort and suggested that the D2M sub‐sample is slightly higher in socioeconomic status (SES) and lower in aggression but higher in stress (Murray, Speyer, et al., 2022). The sub‐sample does not, however, appear to differ from the main z‐proso sample on a range of other characteristics, including ADHD symptom levels, internalising problems, and substance use (Murray, Speyer, et al., 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal of the present study is thus to explore the association between negative parenting practices in childhood, student–teacher relationships in adolescence, and NA, EI and EL in young adulthood employing methods that overcome the limitations of previous studies by using longitudinal and ecologically valid data from the longitudinal Zurich Project on the Social Development form Childhood to Adulthood (z‐proso; Ribeaud et al, 2022) and its EMA sub‐study, Decades‐to‐Minutes (D2M; Murray et al, 2022). The EMA data will be used in conjunction with longitudinal measures to build a trajectory of the etiology of NA, EI and EL using a DSEM model.…”
Section: Introductionmentioning
confidence: 99%